All are called : mission strategies for home - Amorese, Rubem (Regnum Books International, 2019)
So, where are missionaries born? Where do they come from? Where do they go to? What do they do? Why do they do what they do? Missionaries come from Jerusalem, and go to Judea, Samaria and to the whole world, don't they? But, for Rubem Amorese, Jesus' command to "Go!" doesn't mean that you can't stay in Jerusalem, the city where you are born, and being a missionary is not really just a question of geography. All Are Called: Missionary Strategies for Home points towards a broader and more biblical understanding of the word 'missionary'.